Loss given default adjusted workout processes for leases - Miller, Patrick; Töws, Eugen (Journal of Banking & Finance, 2018)
Employing defaulted leases, this study divides the loss given default (LGD) into two parts. So far, LGD has been regarded as a holistic measure of risk. However, considering the specifics of leases, we distinguish between asset-related and miscellaneous revenues of the workout process in order to calculate component LGDs. We introduce a multi-step approach to estimate the overall LGD of leases, based on its economic composition. The performance is assessed out-of-sample and out-of-time. We find that our approach generates stable and accurate estimations. Moreover, using the estimated component LGDs, we obtain valuable information regarding the debt collection procedure that lead to monetary advantages for the lessor.